Capital-based Pension Funds: The Question of Risk Sharing - Ząbkowicz, Anna (Central and Eastern European Economic Review, 2018)
Capital-based pension funds are built from the contributions of their participants and are invested in financial assets. Failed investments cause a fund’s capital to shrink, which generates a risk of low pension benefits and/or the insolvency of the fund. The risk can be shared between contributors, pension fund management companies, and the state (under a mandatory pension funds regime). This article attempts to emphasise that, particularly in the case of old-age insurance, the problem of who runs the most risk is pivotal and deserving of greater concern than the issue of whether the rate of return on investment is high enough. The aim is to draw attention to this rather neglected aspect of the recent reforms of the old-age insurance industry.The method relies on an ordered analysis founded on a review of the relevant subject literature. The point is made that the change from the Defined Benefit (DB) to the Defined Contribution (DC) formula shifts most of the risk onto contributors. On the other hand, this change makes the business relatively safe for private insurers and banks and reduces pressure on the public finance balance sheet. The shift from DB to DC schemes is rather common in Europe, hence the main issues tackled in the article are relevant to a fairly big group of countries (including Poland).The article discusses the issue of risk-sharing in reference to the modern experience of Chile, a country that pioneered changes with respect to capital-based pensions and DC schemes. It concludes that the element of social solidarity recently introduced into the Chilean system brings some relief to low-income workers and also supports the longevity of the fully-funded Defined Contribution system.